1999
DOI: 10.1152/ajprenal.1999.276.6.f857
|View full text |Cite
|
Sign up to set email alerts
|

d-Serine is reabsorbed in rat renal pars recta

Abstract: d-Serine normally contributes up to 3% to total plasma serine and up to 23% in chronic renal failure. d-Serine is metabolized by tubular d-amino acid oxidase (D-AAO), and highd-serine plasma levels are nephrotoxic; both events are localized in the straight part of the proximal tubule. We therefore investigated if and howd-serine is reabsorbed there. We microinfused14C-labeledd- or -l-serine + [3H]inulin into early proximal (EP), late proximal (LP), or early distal (ED) tubule sections of superficial nephrons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 23 publications
(33 reference statements)
0
48
0
Order By: Relevance
“…Direct D-serine administration may be problematic due to its accumulation in several tissues and nephrotoxic effects (41). Our results point to the feasibility of designing serine racemase ligands to stimulate Lserine racemization while impairing ␣,␤-elimination.…”
Section: Discussionmentioning
confidence: 81%
“…Direct D-serine administration may be problematic due to its accumulation in several tissues and nephrotoxic effects (41). Our results point to the feasibility of designing serine racemase ligands to stimulate Lserine racemization while impairing ␣,␤-elimination.…”
Section: Discussionmentioning
confidence: 81%
“…We concluded from our results that filtered D-serine is able to enter the pars recta cells across their apical membrane (38,41). The apical uptake carrier has a very low stereospecificity for serine (41) and alanine (10,38) and is, therefore, different from that in the proximal convolution (39). The colocalization of exclusive reabsorption and metabolism of D-serine makes the pars recta the tubule site for recycling the carbon structure of D-amino acids and, at the same time, the target of D-serine nephrotoxicity.…”
mentioning
confidence: 63%
“…In a last set of experiments, we tested whether AIB has an inhibitory effect on D-serine reabsorption in the proximal tubule, thereby preventing D-serine nephrotoxicity. In earlier studies, we characterized D-serine reabsorption in rat kidney in vivo et situ in detail (39,41). We found that D-serine is only reabsorbed in the S 3 segment of the rat proximal tubule by a high-capacity/low-affinity transport system (K m Ϸ 20 mmol/l).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In renal, the colocalization of exclusive reabsorption and metabolism of amino acids makes the pars recta the tubule site for the recycling of the carbon structure of D-amino acids [27]. Nonetheless, the great excess of serinuria (12.0±0.2 mg/mL) by normal SD rats ( Table 6) was really astonishing.…”
Section: Discussionmentioning
confidence: 98%